(untitled) (Revista Sistemas de Producción Agroecológicos, 2024)
Regarding report #35 of the multi-country Mpox outbreak, generated on August 12 of this year by the World Health Organization (WHO, 2024), where epidemiological data on this emerging disease of zoonotic origin are collected, which describe the behavior of this disease in the population from January 1, 2022 to June 30, 2024. There are 99,176 confirmed cases of Mpox and 208 deaths distributed in 116 countries. Likewise, according to the long-term risk assessment of Mpox until August 2024, the risk is HIGH for the Democratic Republic of the Congo (DRC) and neighboring countries, which mainly affects adults and spreads predominantly through sexual contact (linked to clade Ib). Likewise, HIGH for the DRC where mpox is endemic, mainly affects children and spreads through multiple modes of transmission (linked to clade Ia). MODERATE risk for Nigeria and countries in West, Central and East Africa where mpox is endemic, affects children and adults, and spreads through multiple modes of transmission (linked to clades I and II). MODERATE risk for countries in Africa and globally where outbreaks primarily affect men who have sex with men and spread predominantly through sexual contact (linked to clade IIb).